Pelatihan Pembuatan Katalog Produk Berbasis Digital Guna Meningkatkan Pemasaran Bagi Grup Jual Beli Online - Evi Fajriantina Lova; Rina Rachmawati; Rokiyah Rokiyah; Ahsani Maulidina; Farida Ulfa; Ane Fany Novitasari (I-Com: Indonesian Community Journal, 2024)
The online buying and selling group RW.009 Bukit Cemara Tidar, Malang City, is a WhatsApp group created during the Covid 19 pandemic in mid-2020. Until now, this group still exists and many new business people have joined the group, this means there is potential to develop MSMEs through this group. There is a problem, that the marketing carried out is still conventional, for example product offerings are still rudimentary without paying attention to appropriate promotional methods. This makes it difficult for consumers to find product information, beside that the appearance is also less attractive. The implementation method used is a combination of training and community education. The results of service activities show changes in online marketing. If previously business actors carried out online marketing in a conventional manner, after this service activity was more attractive, neat and conceptual, with the existence of a product catalog.